Cuscohoplininus pagoreni: a new genus and species of Hoplinini stilt bug from Peru (Heteroptera: Berytidae) - Dellapé, Pablo Matías (2007)
The Berytidae or stilt bugs are a cosmopolitan family of lygaeoid bugs, which are slender, elongate insects, with generally cylindrical bodies and very long, slender antennae and legs. Members of the tribe Hoplinini are characterized by the lack of a distinct metapleural scent channel and the possession of a dorsally directed process on the caudal edge of the male genitalia capsule (absent in Xenoloma and Cuscohoplininus). In this paper, we described the new genus and species Cuscohoplininus pagoreni from Peru. Scanning electron micrographs are provided to illustrate taxonomically important structures. Among the eight genera known in the tribe Hoplinini, the new genus Cuscohoplininus resembles Parajalysus in general aspect and size, but can be easily distinguished by the following characters: Parajalysus is characterized by the four large, erect pronotal spines, one centered on the anterior lobe, and on the posterior lobe, one at each humeral angle and one at the base of the meson; whereas, Cuscohoplininus has a single spine on the anterior pronotal lobe, an elongate scutellar spine (a tubercle is present in Parajalysus), and lacks a process on the caudal edge of the male genitalia capsule.